(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article presents the results of the study of some ornamental herbaceous perennials in the Gareev Botanical Garden. of NAS KR. Based on many years of research, their decorative qualities, vegetation periods, and use in landscaping are described.